2021
DOI: 10.18632/genesandcancer.214
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of prostate cancer using novel synthetic DNA vaccines targeting multiple tumor antigens

Abstract: Prostate cancer is a prevalent cancer in men and consists of both indolent and aggressive phenotypes. While active surveillance is recommended for the former, current treatments for the latter include surgery, radiation, chemo and hormonal therapy. It has been observed that the recurrence in the treated patients is high and results in castration resistant prostate cancer for which treatment options are limited. This scenario has prompted us to consider immunotherapy with synthetic DNA vaccines, as this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Immunoblotting. Protein extraction, denaturation, and Western blotting were performed as previously described (29,60,61). Membranes were blotted with anti-phospho-p44/42 MAPK (Erk1/2) (Thr202/Tyr204) (9101, Cell Signaling) and anti-p44/42 MAPK (Erk1/2) (4695, Cell Signaling).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting. Protein extraction, denaturation, and Western blotting were performed as previously described (29,60,61). Membranes were blotted with anti-phospho-p44/42 MAPK (Erk1/2) (Thr202/Tyr204) (9101, Cell Signaling) and anti-p44/42 MAPK (Erk1/2) (4695, Cell Signaling).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with other candidate vaccines, splenocytes of mice immunized with STEAP1 and PAP-SEV showed a lower immune response. The enhanced delivery of these DNA vaccines mediated by the electroporation of plasmid (EP) can produce PCAA-specific CD8+T cells and increase their levels in tumor microenvironments, thereby improving the survival of mice carrying prostate cancer 19 . Although it is often reported that EP can increase the immunogenicity of vaccines, the conversion of this technique into human trials is slightly 2-3 times higher than that of simple injection of naked DNA 20 .…”
Section: Dna Vaccinementioning
confidence: 99%
“…Given its localization to surface cell–cell junctions, particularly that of the prostatic secretory epithelium, STEAP1 is a promising target for T-cell and antibody-based immunotherapy [ 61 , 62 ]. Because STEAP1 is overexpressed in malignant prostate tissue but expressed at low levels in normal prostate tissue, STEAP1 is an ideal therapeutic target ( Table 1 ) [ 59 , 60 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Steap1–4 As Biomarkers and Therapeutic Targets For Prostate ...mentioning
confidence: 99%
“…In vitro cytotoxicity assays demonstrated that these epitopes induced strong CTL-mediated antitumor activity [ 80 ]. Other approaches for targeting STEAP in PCa include fusion protein vaccines, RNA–lipoplex vaccines, recombinant viral vaccines, DNA vaccines, and CAR-T cells [ 64 , 65 , 66 , 67 , 73 ]. These studies are promising, and there is much work to do before they can be translated into PCa therapeutics.…”
Section: Steap1–4 As Biomarkers and Therapeutic Targets For Prostate ...mentioning
confidence: 99%